Effect of connector size and design on the fracture resistance of monolithic zirconia fixed dental prosthesis - Ali Hafezeqoran; Roodabeh Koodaryan; Yasser Hemmati; Ayshin Akbarzadeh (Tabriz University of Medical Sciences, 2020)
Background. Designing a high strength all-ceramic fixed partial denture with favorable esthetics can be challenging for clinicians; this study aimed to evaluate the effect of connector size and design on the fracture resistance of monolithic zirconia fixed dental prostheses. Methods. Two groups of twenty 3-unit monolithic zirconia (Sirona inCoris TZI, Sirona Dental Systems GmbH) bridges, extending from the mandibular first premolar to the first molar with different connector sizes (9 mm2 and 12 mm2 ), were divided into two subgroups with different connector designs (round and sharp). The specimens were subjected to the three-point bending test to obtain the fracture-bearing load. The results were reported using descriptive statistics (mean ± standard deviation). Mann-Whitney U test was used to compare the fracture load in two types of designs for each connector size and two connector size types for each connector design. The significance level was considered at P<0.05. Results. The minimum failure load was related to the group with a 9-mm2 connector size and a sharp embrasure design (1054.4±133.89 N), and the highest mean value belonged to the group with 12-mm2 connector size and rounded embrasure design (1599.8±167.09 N). Mann-Whitney U test indicated a significant difference between the mean failure load of the rounded and sharp embrasure designs in the 9-mm2 connector size (P=0.007). However, the difference was insignificant in the 12-mm2 connector size (P=0.075). Conclusion. Sharp embrasure design is not recommended for high-stress areas with restricted occlusogingival height. A 9-mm2 connector size for 3-unit monolithic zirconia fixed dental prosthesis (FDP), which is recommended by the manufacturer, should be used more cautiously